(untitled) (Indian Journal of Animal Production and Management, 2014)
The study was conducted on 18 lactating Murrah buffaloes to know the effect of different regime of watering on water intake and dry matter intake( DMI). The different regime of watering were as group-I ad lib watering, group-II, watering before 1hr of milking, group III, watering after 1 hr of milking and group-IV, watering before and after 1hr of milking. The overall DMI (kg/day/animal) for the experimental group was 12.22± 0.06 12.15±0.06, 11.73±0.06 and11.30±0.06 in group IV II, III & I respectively. The statistically the overall DMI significantly (P<0.01) varies among the group. The water intake were 46.0±0.57, 52.0±0.65, 49.7±0.56 and 53.0±0.62 in the groups I, II, III and IV respectively. Overall water intake (lit/ day) varies significantly (P<0.01) among the groups. The concentration of sodium in the group III has a significantly higher sodium concentration as compare to group I & IV but group III did not differ from group II. The data of potassium concentration revealed that all the treatment group did not differ significantly. The hematological parameters like RBC & PCV also not significantly varies among the groups.